INTENSITAS PENGGUNAAN GOOGLE TRANSLATE TERHADAP MAHASISWA BAHASA ARAB DALAM PENERJEMAHAN BAHASA ARAB - Kurniawan, Asep; Tatang; Ali Tantowi, Yusuf (JURNAL ILMU PENDIDIKAN, 2024)
The Arabic translation process is one of the challenges for Arabic Language Education students. So in this era of increasingly sophisticated technology, the use of cell phones is no longer strange in helping students in learning, including in learning to translate Arabic into Indonesian or vice versa. This research aims to find out and analyze the intensity of Google Translate towards the Arabic translation process. This type of research is qualitative and the data collection technique uses a questionnaire in the form of a questionnaire. The results of this research show that the intensity of use of Google Translate in the Arabic translation process is quite large. So Google Translate can be a reference for use in translation.